2014
DOI: 10.7589/2014-03-065
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey for Cross-Species Pathogens in Urban Coyotes (Canis latrans), Colorado, USA

Abstract: ABSTRACT:As coyotes (Canis latrans) adapt to living in urban environments, the opportunity for cross-species transmission of pathogens may increase. We investigated the prevalence of antibodies to pathogens that are either zoonotic or affect multiple animal species in urban coyotes in the Denver metropolitan area, Colorado, USA, in 2012. We assayed for antibodies to canine parvovirus-2, canine distemper virus, rabies virus, Toxoplasma gondii, Yersinia pestis, and serotypes of Leptospira interrogans. Overall, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Neither test has been validated for use in wild carnivores because of potential inaccuracy or cross-reaction with other agents (Greiner and Gardner 2000). Currently, there are no serological tests validated for the wild carnivores sampled in our study, but the tests developed for domestic dogs and cats are widely used in the testing of wild carni- vores (Malmlov et al 2014;Orozco et al 2014a, b;Nelson et al 2012;Curi et al 2012;Furtado et al 2013;Nava et al 2008;Fiorello et al 2007;Deem and Emmons 2005).…”
Section: Laboratory Analysesmentioning
confidence: 96%
“…Neither test has been validated for use in wild carnivores because of potential inaccuracy or cross-reaction with other agents (Greiner and Gardner 2000). Currently, there are no serological tests validated for the wild carnivores sampled in our study, but the tests developed for domestic dogs and cats are widely used in the testing of wild carni- vores (Malmlov et al 2014;Orozco et al 2014a, b;Nelson et al 2012;Curi et al 2012;Furtado et al 2013;Nava et al 2008;Fiorello et al 2007;Deem and Emmons 2005).…”
Section: Laboratory Analysesmentioning
confidence: 96%
“…Comparative lack of disease in coyotes is notable given the intense surveillance of radio-collared coyotes in Cook County (Basics of studying coyotes, ) and documented high CDV seroprevalence in this species (C. Chu, personal communication). High CDV seropositivity and an absence of fatal disease has also been noted in coyotes elsewhere suggesting frequent exposure without significant morbidity or mortality [ 22 , 23 , 24 ]. These findings suggest that pathogenicity is not determined solely by viral intrinsic factors and that host-virus interactions likely play a role in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate was higher in mustelids (43% -504/1,173), followed by bears (23% -95/459) and canids (15% -1,079/7,291) 28 . Malmlov et al reported a 28% (7/25) serum prevalence in coyotes 26 .…”
Section: Yearmentioning
confidence: 99%
“…In the USA, serological surveillance is performed on a wide variety of mammals, as it is thought that this procedure is more sensitive, and allows better assessment of plague behavior and circulation in focal areas [25][26] . Lowell et al 27 state that surveillance involving many species provides better coverage of plague activity than monitoring a single species.…”
Section: Yearmentioning
confidence: 99%
See 1 more Smart Citation